?HETEROTIC RESPONSE OF Fl SORGHUM IIYBRIDS TO NaCI SALINITY AT EARLY STAGE OF PLANT GROWTH - Azhar, Faqir Muhammad; Hussain, Syed Sarfraz; Mahmood, Ishtiaq (Biological Sciences - PJSIR, 1998)
The analysis of variance revealed highly significant differences among 12 genotypes (6 parents and 6 F, hybrids) of sorghum, four NaCI solutions and interaction components. The heterotic response of the six hybrids was studied in LOa 111Mand 150 mM NaCI solution. In 100 mM NaCI, all the hybrids manifested positive and significant amount of heterosis over mid-parent, and when compared with their better parents four hybrids displayed significant increase in root length. Under 150 mM salinity level root length of all the genotypes was inhibited severely; only two hybrids i.e. B-378 Red Lan x QL 10 and INRA 209 X B-378 Red Lan yielded best heterosis and heterobeltosis. The results suggested that manifestation of non-significant and significant heterosis over mid parent is due to the genes acting additively and non-additivelly, respec- tively, whilst the occurrence of heterobeltosis is by the genes with overdominance.